Simultaneous pre-treatment of dietary Moringa oleifera leaf meal with polyethylene glycol and fibrolytic enzymes: Effect on growth performance, physiological indices, and meat quality parameters in jumbo quail - Mulaudzi, Anzai; Mnisi, Caven Mguvane; Mlambo, Victor (Frontiers in Animal Science, 2022)
The utility of Moringa oleifera leaf meal (MOLM) as a source of biologically active substances and nutrients for Jumbo quail is limited by high concentrations of condensed tannins and fibre. Simultaneous application of polyethylene glycol (PEG), a tannin-binding compound, and exogenous fibrolytic multi-enzymes could ameliorate antinutritional effects of condensed tannins and fibre thus improving MOLM utilization in quail diets. This study investigated the effect of pre-treating dietary MOLM with PEG and fibrolytic enzymes on live performance, blood parameters, visceral organs, and carcass and meat quality characteristics in Jumbo quail. A total of 381, two-week-old quail chicks (57.5 ± 3.95 g live-weight) were randomly distributed to six dietary treatments replicated six times. The treatments were: T1 = a standard grower diet containing untreated MOLM (10%); T2 = a standard grower diet containing MOLM (10%) pre-treated with 5.4% PEG; and a standard grower diet containing MOLM (10%) pre-treated with 5.4% PEG and 1.25% (T3), 1.50% (T4), 1.75% (T5) and 2.0% (T6) fibrolytic multi-enzymes. Graded levels of enzymes did not induce linear or quadratic effects for overall feed intake, feed conversion efficiency, hematological, carcass, and meat quality parameters in response to increasing fibrolytic enzyme levels. However, weight gain in week 3 quadratically responded [R2 = 0.117, P = 0.043]. Three-week old birds reared on T3 had lower (p < 0.05) weight gains (40.9 g/bird) than those reared on the other treatment groups. Birds reared on T6 diet had longer caecum (14.1 cm) than those reared on T2, T3, T4 and T5 whose caeca lengths did not differ (P > 0.05). Birds reared on diet T5 had shorter small intestines (59.5 cm) than those reared on T1 and T2 diets. It can be concluded that simultaneous pre-treatment of dietary MOLM with PEG and fibrolytic enzymes did not improve live performance, blood parameters, and carcass and meat quality traits, but affected some visceral organ sizes in Jumbo quail.